How do you solve 5d - 6= 3d + 9?

3 Answers
Sep 13, 2017

Subtract 3d from both sides then add 6 to both sides,
then divide by the coefficient of the variable to get d=7 1/2

Explanation:

Given
color(white)("XXX")5d-6=3d+9

By subtracting 3d from both sides we can remove any term containing a variable from the right side:
color(white)("XXX")5d-6color(blue)(-3d)=3d+9color(blue)(-3d)

color(white)("XXX")2d-6=9
Now, if we add 6 to both sides we can remove any constant term from the left side:
color(white)("XXX")2d-6color(blue)(+6)=9color(blue)(+6)

color(white)("XXX")2d=15

Finally dividing both sides by 2 reduces the left side to a unit variable:
color(white)("XXX")2dcolor(blue)(div 2)=15color(blue)(div 2)

color(white)("XXX")d=7 1/2

Sep 13, 2017

5d-3d=6+9
2d=15
d=15/2
d=7.5

Sep 13, 2017

7.5

Explanation:

5d-6=3d+9
First, we will remove 3d from both sides.
5d-6(-3d) = 3d+9(-3d)
The -3d in the brackets represent what we will remove.
That will equal 2d-6=9
9+6=15
15=2d
1d=15/2=7.5
Solved!